Beyond daily values: are day-to-day and albumin-adjusted ratios of IL-6, PCT, and CRP better predictors of ventilator-associated pneumonia? - Bexten, Tobias; Haarmeier, Golo-Sung; Klein, Johann; Lindner, Holger A.; Rahali, Chaimae; Schneider-Lindner, Verena (Life, 2025)
Background: Ventilator-associated pneumonia (VAP) is a frequent complication in neurosurgical intensive care patients. This leads to prolonged mechanical ventilation, increased 30-day mortality rates, and extended hospital stays. However, early diagnosis remains a challenge. Biomarkers, such as IL-6, PCT, and CRP, are considered a cornerstone for recognizing VAP and initiating early treatment. Only a very limited number of studies have compared IL-6, PCT, and CRP, focusing on day-to-day dynamics and their albumin ratios. Therefore, we investigated whether, compared with their daily levels, the day-to-day dynamics and albumin-adjusted ratios of IL-6, PCT, and CRP offer improved diagnostic value for VAP. Second, we investigated these biomarkers in patients treated for VAP who did not meet the criteria for VAP. Methods: In this exploratory, matched case-control study, we investigated 171 neurosurgical ICU patients. Daily biomarker levels, their dynamics, and ratios to serum albumin were assessed beginning four days before VAP. Logistic regression and receiver operating curve (ROC) analyses were performed to evaluate the association between each biomarker and VAP. Results: IL-6 and its day-to-day dynamics demonstrated the largest differences between VAP patients and nonVAP patients (r = 0.631; r = 0.452) and were associated with VAP, yielding AUCs of 0.816 and 0.726, respectively. In contrast, for PCT, we did not demonstrate any associative utility, whereas CRP showed a significant, moderate effect size on the day of VAP occurrence (p = 0.015 *; r = 0.351). We could not demonstrate any superiority in the day-to-day dynamics or the albumin-adjusted ratios compared to the daily values. For patients who were treated for VAP without fulfilling the criteria for biomarkers, we did not observe any significant difference from nonVAP patients.
Veröffentlicht: 1. November 2025
Gesehen am 26.01.2026